METHODOLOGY FOR IMPROVING THE ACTIVITY OF PRIMARY CLASS SUPERVISORS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The article analyzes the current issues of the methodology of improving the activities of elementary school leaders and presents recommendations on the problem.